Influence Leadership and Health and Safety (K3) on Employee Performance PT. PLN (Persero) UPJ-Central Semarang Engineering - Aprilia, Riana; Prihatini, Apriatni Endang; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
Every company needs a resource that has an important influence to achieve success. Human resource management play an active role in improving employee performance through a number of variables that influence including leadership and occupational health and safety (K3). Based on the existing problems in this study was a decrease in the performance of employees of PT. PLN (Persero) UPJ-Central Semarang technique in 2014 in repairing damaged transformers, transformer damage that should be the target of 25 units, but in reality to 39 units and the target shrinkage transformer is supposed to 8.55% but in fact 19.62%. The aim of this study was to determine the effect of leadership and occupational health and safety (K3) on the performance of employees of PT. PLN (Persero) UPJ-Central Semarang techniques. This type of research is explanatory research. The population in this study are employees of PT. PLN (Persero) UPJ Middle Semarang engineering section with a sample size of 50 respondents. Census sampling techniques. The technique of collecting data using questionnaires and interviews. The analytical method used is validity, reliability, cross tabulation, correlation, determination, regression analysis, the significance test with SPSS. Research, leadership is in excellent health and safety (K3) is quite good, and the performance as very good. It shows when the leadership is getting better and with the implementation of occupational health and safety (K3) is good, then the performance will increase. Researchers suggest that high employee performance it should be more assertive leadership, solid, and clear in giving instructions, so that each employee can capture well the instructions given by the leader and carry out their work according to the instructions of work that has been directed. Listening to complaints from employees, employee supervision until the work is completed on time. More attention to the work tools and equipment that are not proper to use immediately replaced a new one, so that employees feel comfortable in their work.